1980
DOI: 10.1073/pnas.77.11.6371
|View full text |Cite
|
Sign up to set email alerts
|

Redox conformation changes in refined tuna cytochrome c.

Abstract: Tuna ferrocytochrome c and ferricytochrome c have been refined independently at high resolution (1.5 A and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(67 citation statements)
references
References 40 publications
9
58
0
Order By: Relevance
“…Second, modification of the propanoic acid side chains of the C8 and C12 positions at the B-and C-rings has a substantial effect on chromophore binding, suggesting that free-acid elements are required for this event. A similar result has been reported already for pea PHYA (31), raising the possibility that chromophore binding is dictated by the electrostatic interaction between propanoic acid side chains and basic amino acid residues such as Arg or Lys of the phytochrome apoprotein (31), perhaps analogous to heme binding in cytochrome c (50). Our present data support this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Second, modification of the propanoic acid side chains of the C8 and C12 positions at the B-and C-rings has a substantial effect on chromophore binding, suggesting that free-acid elements are required for this event. A similar result has been reported already for pea PHYA (31), raising the possibility that chromophore binding is dictated by the electrostatic interaction between propanoic acid side chains and basic amino acid residues such as Arg or Lys of the phytochrome apoprotein (31), perhaps analogous to heme binding in cytochrome c (50). Our present data support this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…Two propanoate side chains of all tetrapyrrole chromophores in allophycocyanin are accessible from the surface of the protein molecule (51). The two propanoic side chains of the heme in cytochromes (52), myoglobin (53), and hemoglobin (54) also are exposed from the heme pocket, but those of mitochondrial cytochrome c are buried in a crevice (50). In this regard, PhyB appears to resemble the mitochondrial cytochrome c. The phytochrome protein seems therefore to differ from other Table 1).…”
Section: Discussionmentioning
confidence: 85%
“…previous cytochrome c crystal structures (35,43) have shown that structural differences are partially localized to the binding site of cytochrome c for its BC1 binding partner (44); the results presented herein agree well with these studies.…”
Section: Comparison Of Rm-encapsulated Cytochrome C With Othersupporting
confidence: 82%
“…Electron transfer side of the molecule [8]. Thus the binding site for cytochrome c must be a cleft of diameter close to that of the cytochrome c molecule.…”
Section: Thionitrobenzoatementioning
confidence: 99%